2011
DOI: 10.1080/00028487.2011.638584
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Metapopulation Dynamics in Shortnose Sturgeon in the Southern Part of Their Range

Abstract: The shortnose sturgeon Acipenser brevirostrum is one of the most endangered members of the sturgeon family because of overexploitation, depressed population levels, and a shrinking range. The lack of historical data on shortnose sturgeon populations has led to an increase in sturgeon research over the last three decades; however, most recent studies have not focused on southern populations. The objective of this study was to estimate the abundance, annual survival, and temporary emigration rates of shortnose s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Interestingly, previous studies have documented similar patterns in other Shortnose Sturgeon populations. A recent study of Shortnose Sturgeon in the Ogeechee River, Georgia (Peterson and Farrae 2011), documented a comparable level of population variability from 2007 to 2009 (CV = 33.0%). Although Bain et al (2007) did not provide a quantitative estimate of variability in annual adult abundance, their data showed that adult abundance in the Hudson River Shortnose Sturgeon population was steady over the 4 years of their study.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, previous studies have documented similar patterns in other Shortnose Sturgeon populations. A recent study of Shortnose Sturgeon in the Ogeechee River, Georgia (Peterson and Farrae 2011), documented a comparable level of population variability from 2007 to 2009 (CV = 33.0%). Although Bain et al (2007) did not provide a quantitative estimate of variability in annual adult abundance, their data showed that adult abundance in the Hudson River Shortnose Sturgeon population was steady over the 4 years of their study.…”
Section: Discussionmentioning
confidence: 92%
“…However, genetic evidence indicates that the Ogeechee River population is closely related to that in the Altamaha River (Wirgin et al 2005). The probability of emigration from the Ogeechee population was estimated to be 0.16 (SE = 0.275) and the probability of immigrating was 0.84 (Peterson and Farrae 2011). Thus, the PVA model presented here should be expanded to describe these systems in tandem to account for potential "rescue effects" (Brown and Kodric-Brown 1977) in which extirpated populations may be recolonized by their neighbors.…”
Section: Small Coastal Rivers As Ecological Trapsmentioning
confidence: 96%
“…The spawning migration of Shortnose Sturgeon begins in late winter, but seems to follow different patterns in different rivers. In some rivers (e.g., the Hudson River), adults that are ready to spawn congregate downstream and migrate upstream together (Dovel 1981), and in other rivers, individuals migrate separately (Peterson and Farrae 2011). When the congregation option is simulated, all spawners join a group near a specified downstream location at the start of the breeding season.…”
Section: Reproductionmentioning
confidence: 99%
See 2 more Smart Citations